Surfing the net for software engineering notes. - Doernhoefer, Mark (Software engineering notes.)
The September issue of IEEE Spectrum was dedicated to a special report on failed software development projects. Led by the cover story on the FBI Virtual Case File, also known as Trilogy, the magazine contained several case studies on software projects that blew up during development or shortly after release. Readers of Peter Neumann's RISKS column or books by Yourdon, Glass, and others know that software development failures are noting new.